Crop Agriculture of Bangladesh: Challenges and Opportunities - Mondal, Mohammad H (Bangladesh Journal of Agricultural Research, 2010)
Crop agriculture in Bangladesh is constrained every year by challenges, such as a) Loss of Arabie Land, b) Population Growth, c) Climate Changes, d) Inadequate Management Practices, e) Unfair Price of Produces, and f) Insufficient Investment in Research. In Bangladesh, about 80,000 ha of arable land are going out of production every year. The loss is alarming and needs to be addressed immediately. The land use policy of the government should be updated and implemented immediately to stop further loss of arable land. Another problem to agriculture is the increase in the growth of population. The twin problem of arable land loss and population growth needs to be addressed simultaneously to ensure sustainable crop production. Country's crop production is also affected frequently by flood, drought, and salinity. Varieties/technologies tolerant to these natural hazards need to be developed. Renewable energy, reduction in the use of fossil fuels, and afforestation are recommended to mitigate the adverse effects of climate change. To sustain crop production, chemical fertilizers must be integrated with organic manure and costly non-urea fertilizers should continue to be subsidized. Incidence of pests and diseases has lately become severe due to climate change impacts. Therefore, more varieties resistant to the pests should be evolved. Small and marginal farmers of Bangladesh have limited access to institutional credit. They are not eligible for microcredit of NGOs either. Establishment of a new institution/foundation in line with PKSF is recommended to meet their needs. These farmers do not have farmers' associations or cooperatives to bargain for fair price of their produces. Government might encourage establishment of farmers' cooperatives to ensure fair price of their produces. To make such cooperatives successful, top-down approach by the influentials must be avoided. Investment in agricultural research should as well be raised to at least 2% of GDP to help generate technologies to cope with climate change hazards and disseminate such technologies at farmer's level. Keywords: Crop agriculture; challenges; opportunities. DOI: 10.3329/bjar.v35i2.5886 Bangladesh J. Agril. Res. 35(2) : 235-245, June 2010